Inventing the Future: Yogyakarta City Government’s Policy in Actualizing Smart City (Center for Public Policy and Digital Government Universitas Muhammadiyah Yogyakarta, 2024)
Yogyakarta is a notable tourist destination in Indonesia, known for its abundant cultural legacy, historical significance, and natural splendor. Yogyakarta may improve the experience of travelers by adopting smart city initiatives, which involve the implementation of advanced technology to offer improved information and services. This includes efficient management of transportation, interactive tourist applications, and the development of tourism-friendly infrastructure. Smart technology in a smart city can enhance the citizens' quality of life. In response to these difficulties, the government has implemented several initiatives, one of which involves transforming Yogyakarta into a smart city, or, in other words, a technologically advanced urban area. The government has established an internet and intranet network in Yogyakarta, effectively connecting the city and transforming it into a smart city. The application of the smart city idea in Yogyakarta Municipality yields a wide range of benefits. An example of such a policy is the e-Health policy, which brings about advantages for patients and MCH service users. These benefits include faster and more convenient services, as well as more accurate patient data. The JSS (Jogja Smart Service) application is a significant advancement in the sphere of public services, serving as the first implementation of Smart City and e-government in Yogyakarta.